Real-World Outcomes of Pralsetinib in RET Fusion-Positive NSCLC - Francesca Lucibello, MD; Valérie Gounant, MD, PhD; Mihaela Aldea, MD, PhD; Michaël Duruisseaux, MD, PhD; Maurice Perol, MD; Christos Chouaid, MD; Jaafar Bennouna, MD, PhD; Vincent Fallet, MD; Aldo Renault, MD; Florian Guisier, MD, PhD; Etienne Giroux-Leprieur, MD, PhD; Marie Wislez, MD, PhD; et al. (JTO Clinical and Research Reports)
Introduction: Pralsetinib is a RET inhibitor found to have antitumor activity in advanced, metastatic, RET fusion-positive NSCLC. Objective: To assess real-world efficacy of pralsetinib and treatment sequences in patients with RET fusion-positive NSCLC. Design: Retrospective study of consecutive patients enrolled in the French expanded-access program for pralsetinib from December 1, 2019, to December 31, 2021. Participants: A total of 41 patients with advanced, refractory, RET fusion-positive NSCLC were included. Pralsetinib was administered at a daily dose of 400 mg based on safety and pharmacokinetic outcomes from previous phase 1/2 study. Results: Pralsetinib was administered as second line in 23 patients (56%) and as third line and beyond in 15 patients (37%). After a median follow-up of 26.3 months, pralsetinib was ongoing in 13 patients. Median real-world progression-free survival was 11.8 (95% confidence interval [CI]: 9.3–15.5) months. Objective response rate was 68% (95% CI: 50%–82%), and disease control rate was 89% (95% CI: 75%–97%). Subsequent line of systemic therapy was initiated in 11 patients. Median overall survival from pralsetinib initiation was 23.8 (95% CI: 16.5–not reached) months. Conclusion: In this extensive real-world cohort of patients with advanced or metastatic NSCLC harboring RET fusions, we highlight the antitumor efficacy of pralsetinib, particularly when administered in later treatment lines. We also observe the aggressive nature of disease progression, frequent utilization of chemotherapy and antiangiogenic agents as initial subsequent therapies, and limited insight into resistance mechanisms due to infrequent rebiopsy and genomic profiling at progression.